Development of High Yielding Fusarium Wilt Resistant Cultivar by Pyramiding of “Genes” Through Marker-Assisted Backcrossing in Chickpea (Cicer arietinum L.) - Bharadwaj, C.; Jorben, J.; Rao, Apoorva; Roorkiwal, Manish; Patil, B. S.; Jayalakshmi,; Ahammed, S. Khayum; Saxena, D. R.; Yasin, M.; Jahagirdar, J. E.; Sontakke, P. L.; Pithia, M. S.; et al. (Frontiers in Genetics, 2022)
Pusa 391, a mega desi chickpea variety with medium maturity duration is extensively cultivated in the Central Zone of India. Of late, this variety has become susceptible to Fusarium wilt (FW), which has drastic impact on its yield. Presence of variability in the wilt causing pathogen, Fusarium oxysporum f.sp. ciceri (foc) across geographical locations necessitates the role of pyramiding for FW resistance for different races (foc 1,2,3,4 and 5). Subsequently, the introgression lines developed in Pusa 391 genetic background were subjected to foreground selection using three SSR markers (GA16, TA 27 and TA 96) while 48 SSR markers uniformly distributed on all chromosomes, were used for background selection to observe the recovery of recurrent parent genome (RPG). BC1F1 lines with 75–85% RPG recovery were used to generate BC2F1. The plants that showed more than 90% RPG recovery in BC2F1 were used for generating BC3F1. The plants that showed more than 96% RPG recovery were selected and selfed to generate BC3F3. Multi-location evaluation of advanced introgression lines (BC2F3) in six locations for grain yield (kg/ha), days to fifty percent flowering, days to maturity, 100 seed weight and disease incidence was done. In case of disease incidence, the genotype IL1 (BGM 20211) was highly resistant to FW in Junagarh, Indore, New Delhi, Badnapur and moderately resistant at Sehore and Nandyal. GGE biplot analysis revealed that IL1(BGM20211) was the most stable genotype at Junagadh, Sehore and Nandyal. GGE biplot analysis revealed that IL1(BGM 20211) and IL4(BGM 20212) were the top performers in yield and highly stable across six environments and were nominated for Advanced Varietal Trials (AVT) of AICRP (All India Coordinated Research Project on Chickpea) in 2018–19. BGM20211 and BGM 20212 recorded 29 and 28.5% average yield gain over the recurrent parent Pusa 391, in the AVT-1 and AVT-2 over five environments. Thus, BGM20211 was identified for release and notified as Pusa Manav/Pusa Chickpea 20211 for Madhya Pradesh, Gujarat and Maharashtra, Southern Rajasthan, Bundhelkhand region of Uttar Pradesh states by the Central Sub-Committees on Crop Standards, Notification and Release of Varieties of Agricultural Crops, Ministry of Agriculture and Farmers Welfare, Government of India, for commercial cultivation in India (Gazette notification number S.O.500 (E) dt. 29-1-2021).Such pyramided lines give resilience to multiple races of fusarium wilt with added yield advantage.